2022
DOI: 10.18323/2782-4039-2022-3-2-25-31
|View full text |Cite
|
Sign up to set email alerts
|

The influence of severe plastic deformation on mechanical properties of pure zinc

Abstract: Biodegradable materials, which have the ability to resorb in the body, are new and promising materials for medical implants. Currently, scientists carry out the investigations according to three directions: Mg, Fe, and Zn alloys. Zinc-based alloys and zinc have good solubility in the body, which meets the clinical requirements of implants. However, pure zinc has low mechanical properties, including hardness and tensile strength. Therefore, at present, the world scientific community is seeking ways to improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…However, this level of strength is still insufficient for medical applications starting from 300 MPa [ 7 ]. Application of high-pressure torsion has shown that the grain refinement of pure Zn to the nanoscale increases the UTS of the material up to 260 MPa and ductility up to 40% [ 18 , 19 ]. It has been shown that high-pressure torsion also significantly strengthens Zn-0.5%Cu [ 20 ] and Zn-0.8%Ag [ 21 ] alloys.…”
Section: Introductionmentioning
confidence: 99%
“…However, this level of strength is still insufficient for medical applications starting from 300 MPa [ 7 ]. Application of high-pressure torsion has shown that the grain refinement of pure Zn to the nanoscale increases the UTS of the material up to 260 MPa and ductility up to 40% [ 18 , 19 ]. It has been shown that high-pressure torsion also significantly strengthens Zn-0.5%Cu [ 20 ] and Zn-0.8%Ag [ 21 ] alloys.…”
Section: Introductionmentioning
confidence: 99%